2022
DOI: 10.1093/plcell/koac142
|View full text |Cite
|
Sign up to set email alerts
|

The conjugation of SUMO to the transcription factor MYC2 functions in blue light-mediated seedling development in Arabidopsis

Abstract: A key function of photoreceptor signalling is the coordinated regulation of a large number of genes to optimize plant growth and development. The bHLH transcription factor MYC2 is crucial for regulating gene expression in Arabidopsis thaliana during development in blue light. Here we demonstrate that blue light induces the SUMOylation of MYC2. Non SUMOylatable MYC2 is less effective in suppressing blue light-mediated photomorphogenesis than wild-type MYC2. MYC2 interacts physically with the SUMO proteases SUMO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Only a few studies have reported the model for regulating plant lateral branch development using different light qualities. The photomorphogenesis of plants is induced by light through multiple photoreceptors and abundant related plant morpho-physiological and gene expression processes (Srivastava et al, 2022). The regulatory mechanism of different light qualities on crop morphogenesis is of great significance.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have reported the model for regulating plant lateral branch development using different light qualities. The photomorphogenesis of plants is induced by light through multiple photoreceptors and abundant related plant morpho-physiological and gene expression processes (Srivastava et al, 2022). The regulatory mechanism of different light qualities on crop morphogenesis is of great significance.…”
Section: Introductionmentioning
confidence: 99%
“…Among MYCs, MYC2 is a dominant player regulating plant defense responses, while MYC3 and MYC4 have a redundant role (Niu et al ., 2011, Ortigosa et al ., 2020). Specifically, the role of MYC2 in light-mediated seedling development has been well established (Yadav et al ., 2005, Gangappa et al ., 2010, Gangappa et al ., 2013b, Sethi et al ., 2014, Chakraborty et al ., 2019, Ortigosa et al ., 2020, Srivastava et al ., 2022). However, the role of MYC3 and MYC4 and their interaction with MYC2 in the seedling photomorphogenesis was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Among MYCs, the role of MYC2 in Arabidopsis seedling development is very well established. MYC2 is a key regulator of seedling photomorphogenesis and light-induced gene expression (Yadav et al, 2005, Gangappa et al, 2010, Sethi et al, 2014, Maurya et al, 2015, Chakraborty et al, 2019, Srivastava et al, 2022, Ojha et al, 2023). While the role of MYC2 in light-mediated seedling development has been studied to some extent, that of MYC3 and MYC4 remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…SUMO conjugation does not affect the dimerization of MYC but modulates the interaction of MYC2 with its cognate DNA cis-element and with the ubiquitin ligase plant U-box 10 (PUB10). Moreover, the non-SUMOylatable MYC2 is less stable and interacts more strongly with PUB10; thus, SUMO functions as a counterpoint to the ubiquitin-mediated degradation of MYC2 [ 45 ]. In addition, E3 ubiquitin ligase can also reduce MYC protein level based on Cullin3 and BPM proteins as substrate junctions.…”
Section: Myc2-mediated Ja Signalingmentioning
confidence: 99%